SOCIAL RESPONSIBILITY IN THE QURAN: A COMPARATIVE ANALYSIS OF MIDDLE EASTERN AND NUSANTARA MUFASSIRS - Mahmud, Hamidulllah (STAI Asy-Syukriyyah, 2025)
Responsibility is a fundamental principle that influences human behavior and interaction in society In the context of religious life, the Quran is the main source of moral guidance and ethics for Muslims The study of the concept of responsibility in the perspective of the Quran is important to understand how Islamic teachings shape the understanding and implementation of responsibility. This article discusses the concept of responsibility in the Qur'an by analyzing relevant verses and interpretations of prominent scholars The concept of responsibility towards Allah, fellow human beings, and the environment as well as the benefits for humanity The Qur'an emphasizes the importance of individual awareness of actions and their consequences, and teaches that every individual will be held accountable for their actions in the afterlife. Moreover, the Quran also emphasizes that responsibility is not only personal, but also social This research concludes that a deep understanding of the concept of responsibility in the Quran can be a moral guide for Muslims in their daily lives and contribute positively to society, as goodness, well-being, and balance in life cannot emerge without responsibility. Therefore, it is important for Muslims to reflect on the Qur'anic teachings on responsibility and apply them in the practice of daily life.